Nilai Estetika Tari Tepak Sirih di Kabupaten Rokan Hulu Provinsi Riau - Muawwiyahtul Yusro (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
Tepak sirih, a welcoming dance for honored guests that not only functions as entertainment, but also as a symbol of respect and cultural identity of the Rokan Hulu community. This study aims to examine the aesthetic value of the Tepak sirih Dance in Rokan Hulu Regency, both in terms of movement, music, symbolism, and its function as a cultural identity. Thus, it is expected to contribute to the preservation and development of traditional cultural arts that are ancestral heritage as well as enrich the treasury of dance arts in Riau Province. The research method used is a qualitative method with a Choreographic Aesthetic approach, namely beauty seen through aspects of its choreography. Data collection techniques carried out by researchers consist of observation, interviews, documentation. Data validity techniques used by researchers using source triangulation techniques. Data analysis techniques using Adshead's concept, the results of the research conducted can be concluded that the aesthetic value of the Tepak Sirih Dance in Rokan Hulu Regency is a traditional art work that is rich in aesthetic and Mainland Malay cultural values